Fortification with vitamin D: Comparative study in the Saudi Arabian and US markets - Mir Sadat-Ali; Abdulmohsen Al Elq; Mohammed Al-Farhan; Nazia A Sadat (Wolters Kluwer Medknow Publications, 2013)
Background and Objective: Vitamin D deficiency is common among Saudi Arabian population. To evaluate the current status of vitamin D fortification and calcium content of commonly consumed food items by the Saudi population and to compare it to US data. Setting and Design: Cross-sectional market survey at markets of Eastern Province of Saudi Arabia and State of Illinois, USA. Methods: A dietary survey was carried out for the content of calcium and vitamin D on the most commonly consumed food products by the Saudi population which are suppose to be fortified by vitamin D. The survey included different brands of fresh milk, yoghurt, powdered milk, cheese, ready-to-eat breakfast cereals and orange juice. Vitamin D content in the products studied from the Saudi marketplace was compared with the suggested vitamin D content in the same products according to US Code of Federal Regulations recommendations. Results: The overall calcium content in the processed dairy products is generally higher than the content in fresh dairy products. Vitamin D content in the fresh dairy products varied from 40 IU/L to 400 IU/L. None of the cereals or orange juice in Saudi Arabia contain vitamin D supplement. The vitamin D content in the food items from the Saudi marketplace is mostly lower than recommended by the US Code of Federal Regulations. Conclusion: Most commonly consumed food products by Saudi population which are suppose to be fortified by vitamin D either not fortified or contain an amount less than recommended by guidelines set for US marketplace.